Vibrational power flow in beam-plate structures Part I: Basic theory - Yi, Chuijie; Dietz, Peter; Hu, Xuanli (Computer Assisted Methods in Engineering and Science, 2023)
This paper presents the expressions of Vibrational Power Flow (VPF) in Beam-Plate Structures (BPS). These expressions are derived based on structural dynamics. BPS is composed of a constant cross-section beam and a thin fiat rectangular plate. In expressions the plate is four-edge simply suppored and four-edge fixedly supported, respectively. The numerical calculation of these expressions is implemented. Meanwhile, the different parameters of beam and plate are also considered in the calculation. Finally, the numerical solutions of VPF in BPS are compared with the corresponding the measured VPF. The numerical VPFs have a good agreement with the measured VPF. The results of VPF provide a tool for analyzing vibrational energy transmission between the support roller and the armored plate of tracked vehicles.